Ice Engineering: Ice Jams, Winter 2002-2003 - Morgan, Tina M.; Furman, Linnzi; White, Kate (2004)
Ice jams are accumulations of ice in rivers, lakes, and streams (Fig. 1) that can cause destructive floods upstream that are costly to surrounding communities. Areas downstream from the jam also can be affected if the jam releases suddenly, sending a surge of water and ice downstream. The rapid changes in water levels associated with jams often leave little time to prepare for flooding. Damages caused by ice jams can be extensive, affecting roads, bridges, buildings, and homes. Emergency aid and evacuation during ice jam flooding can be delayed or limited because roads and runways may be forced to close and bridges damaged or destroyed. Disruption of commerce on ice-jammed rivers can temporarily halt transportation of heating fuel and other necessary cargo. Ice movement also affects the environment and can cause severe erosion of riverbeds and banks. Wildlife, fish habitat, and vegetation can be adversely affected by ice. It has been estimated that ice jam damages have cost the United States more than $100 million annually. Engineers at the U.S. Army Engineer Research and Development Center's Cold Regions Research and Engineering Laboratory (ERDC-CRREL) have been working to develop and optimize low-cost structural and nonstructural techniques, such as early warning systems, ice dusting, ice breaking, ice weakening, and ice jam removal techniques, to prevent or alleviate damages caused by ice jams. Methods of predicting ice jam occurrence and severity are also being developed. The original document contains color images.